Synthesis of benzofurans via an acid catalysed transacetalisation/Fries-type O → C rearrangement/Michael addition/ring-opening aromatisation cascade of β-pyrones - Bankar, S.K.; Mathew, Jopaul; Ramasastry, S.S.V. (Royal Society of Chemistry, 2016)
An unusual and facile approach for the synthesis of 2-benzofuranyl-3-hydroxyacetones from 6-acetoxy-β-pyrones and phenols is presented. The synthetic sequence involves a cascade transacetalisation, Fries-type O → C rearrangement followed by Michael addition and ring-opening aromatisation. The versatility of this method was further demonstrated via the synthesis of 4,4a-dihydropyrano[3,2-b]benzofuran-3-ones, furo[3,2-c]coumarins, and spiro[benzofuran-2,2′-furan]-4′-ones. The unexpected cascade event would also provide new possible considerations in the β-pyrone-involved organic synthesis.
Keywords: Benzofuran derivative; Phenol derivative; Acetalization; Aromatization